CONSERVATION OF NATURAL ENEMY AS A BIOLOGICAL CONTROL WITH FISHING ECOSYSTEM MANAGEMENT - Victoria Henuhili; Tien Aminatun (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2013)
This research aims were to collect the diversity of natural enemies lived in rice agroecosystem and to observe which management system of rice agroecosystem can conserve natural enemies.There were two kinds of rice agroecosystem observed in this research, multicropping system (surjan system) and monocropping system (non surjan system). There were two parts of surjan fields, aquatic lower part planted with rice and terrestrial higher part planted with vegetables. The surjan fields were different from non surjan fields that were planted with rice only. Non surjan fields were had one part, that was aquatic part. Natural enemies collecting of surjan fields and non surjan fields was done to get conclusion that which system conserved natural enemies more. This researh results were : (1) Surjan fields had more kinds of natural enemies than non surjan fields; (2) The management system of rice agroecosystem that conserved natural enemies more was multicropping system in surjan fields.